Argentinian Dissident Masculinities as Queer Smmugled Dynamite in Witold Gombrowicz’s Trans-Atlántico (Anclajes, 2018)
A queer reading of Witold Gombrowicz’s Trans-Atlantyk (1953), paying special attention to the novel’s most iconoclastic aspects for the Polish culture. It analyses the construction of Gonzalo, a homosexual character whose non-normative masculinity is contrasted by Gombrowicz with Polish hegemonic masculinities. The role of the Argentinean dissident masculinities, as well as the importance of Gonzalo’s queerness for the interpretation of Trans-Atlantyk are examined through the lens of both Polish and Argentinean queer criticism.
Keywords: Witold Gombrowicz; Argentine and Polish Literatures; Queer Studies; 20th Century; Argentina and Poland